DETERMINANTS OF INDONESIA’S CINNAMON EXPORT VOLUME TO THE UNITED STATES: AN ERROR CORRECTION MODEL APPROACH - Siahaan, Elga Winner Mombun; Yuliana, Lia (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2025)
Cinnamon is one of Indonesia's leading export spice commodities. The United States (US) is the strongest importer country of Indonesian cinnamon. However, since 2013 the volume of Indonesian cinnamon exports to the US has decreased. If this decline continues, it could shift Indonesia's position in the cinnamon export market. This research aims to provide an overview of and analyze the influence of export prices, GDP, production, and exchange rate on Indonesia’s cinnamon exports to the US from 1990 to 2022. The data used are from the Food and Agriculture Organization (FAO), World Bank, and Organization for Economic Co-operation and Development (OECD). This research uses descriptive analysis with graphical analysis and inference analysis with the Error Correction Model (ECM). The results showed that in the long term, decreasing export prices can increase demand for cinnamon exports from the US. In the short term, large production that does not meet the quality standards can reduce cinnamon exports. The increase in US people's income and the strengthening of Rupiah can increase the volume of Indonesian cinnamon exports to the US in both the long and short term.